Effect of magnesium on the properties of LiNbO 3 thin films prepared from polymeric precursors - Simões, A. Z. [UNESP]; Gonzalez, A. H. [UNESP]; Riccardi, C. S. [UNESP]; Cilense, M. [UNESP]; Zaghete, M. A. [UNESP]; Stojanovic, B. D. [UNESP]; Tangastev, A.; Setter, N.; Varela, José Arana [UNESP] (My University, 2002)
The effect of magnesium addition on the phase formation, microstructure and electric and ferroelectric properties of LiNbO 3 thin films prepared through polymeric precursors was analyzed. By X ray diffraction no secondary phase was observed with the increase of magnesium concentration. Comparing to pure LiNbO 3, the addition of 0.5 and 1.0 mol% of Mg +2 increased of the dielectric constant, while 2.0 mol% decreased it. It was noticed that the increase in additive concentration decreases the ferroelectric remanent polarization and increases the coercive field. © 2002 Taylor & Francis.
Keywords: Electrical properties; LiNbO 3; Thin films; Ferroelectric properties; LiNbO3; Phase formation; Polymeric precursors; Concentration (process); Electric properties; Ferroelectricity; Lithium niobate; Magnesium printing plates; Microstructure; Phase composition; X ray diffraction